Pelatihan dan Pendampingan Penelitian Tindakan Kelas bagi Guru SMP Aisyiyah Muhammadiyah 3 Malang - Putra, Candra Rahma Wijaya; Andalas, Eggy Fajar; Hudaniah, Hudaniah (University of Merdeka Malang, 2021)
Teachers must be able to increase the standard of their student's education. Various innovations in improving the quality of learning can be done through Classroom Action Research. However, the facts show that the productivity of teachers at SMP 'Aisyiyah Muhammadiyah 3 Malang has not shown significant development. As part of efforts to improve the quality of student learning in class, many teachers have not been able to implement Classroom Action Research. Therefore, this service seeks to provide classroom action research training assistance to teachers of SMP 'Aisyiyah Muhammadiyah Malang. This service program is carried out in four structured activities, namely sharing, concept expository, training and mentoring, and writing research articles. Through the activities that have been carried out, it was found that the main cause of the absence of the research being conducted was motivation. Through psychological strengthening and intensive mentoring, supported by a strategy to develop worksheet instruments, can provide significant results. Teachers of SMP 'Aisyiyah Muhammadiyah 3 Malang can design and produce classroom action research.